2013
DOI: 10.3892/ol.2013.1700
|View full text |Cite
|
Sign up to set email alerts
|

Impact of radiation therapy on survival in patients with triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) has a poorer prognosis compared with other sub-groups. In the current study, survival associated with locoregional treatment of females with TNBC was investigated. Specifically, 468 patients with stage I–III TNBC treated between 2002 and 2009 were identified. Data included patient and tumor characteristics, treatment received and survival. Data were compared using χ2 and Fisher’s exact tests, as well as MANOVA. Kaplan-Meier curves were generated. The study cohort had a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 14 publications
2
35
4
1
Order By: Relevance
“…Individual study authors were also contacted to obtain frequencies not reported in the original article. One study [24], through personal communication with the authors, provided anonymous individual patient data which enabled its inclusion in specific subgroup analysis. The principal quantitative synthesis involved a comparison of BCT and PMRT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Individual study authors were also contacted to obtain frequencies not reported in the original article. One study [24], through personal communication with the authors, provided anonymous individual patient data which enabled its inclusion in specific subgroup analysis. The principal quantitative synthesis involved a comparison of BCT and PMRT.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled HR was 0.57 (95% CI 0.36-0.88), Figure 4; moderate heterogeniety was present (Pheterogeniety =0.07, I 2 = 50.5%). There was little difference when the analysis was restricted to four studies [17,18,24,29] There was no statistically significant interaction between disease stage and BCT/PMRT on overall survival, Pinteraction= 0.983. Combining data from two studies [18,24], the effect of age at diagnosis on overall survival comparing PMRT and BCT to mastectomy only was examined, the corresponding pooled effect estimates were HR 0.30 (95% CI 0.11-0.82) and HR 0.22 (95% CI 0.04, 1.13) age <40 years, HR 0.76 (95% CI 0.37-1.58) and HR 0.38 (95% CI 0.11, 1.31) aged 40-64 years, and HR 0.67 (95% CI 0.14-3.18) and HR 0.79 (95% CI 0.22-2.76) aged ≥65 years respectively, Figure 6 (online only).…”
Section: Overall Survivalmentioning
confidence: 92%
See 2 more Smart Citations
“…This finding contradicts Clark et al [30] who suggested that breast irradiation does not affect survival and Whelan et al [31] who suggested that radiation reduces risk. Steward et al's study [32] showed that adjuvant radiation improved survival of patients undergoing breast-conserving therapy. This finding is similar to our case where combination of surgery and radiation shows significant improvement in survival.…”
Section: Discussionmentioning
confidence: 99%